2012
DOI: 10.1089/dna.2011.1406
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase Gene Polymorphisms (G894T, 4b/a and T-786C) and Preeclampsia: Meta-Analysis of 18 Case–Control Studies

Abstract: Studies investigating the association between endothelial nitric oxide synthase (eNOS) gene polymorphisms and preeclampsia reported contradictory or nonconclusive results. We performed a meta-analysis of 18 genetic association studies that examined the relationship between preeclampsia and the G894T, 4a/b and T-786C polymorphisms of the eNOS gene. Subgroup analysis by ethnicity and potential sources of heterogeneity and bias were explored. The MEDLINE, EMBASE, and Google Scholar databases were searched to acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 87 publications
(147 reference statements)
1
7
0
2
Order By: Relevance
“…In contrast, the rs2070744 (T>C) variant (T786C mutation) was reported to lack an association with EH in Chinese Kazakh and Japanese groups (Kajiyama et al, 2000;Deng et al, 2007). Consistent with these findings in other ethnic populations, such as Chinese Han (Niu et al, 2011;Chen et al, 2012), Hani (Tang et al, 2008), Yi (Tang et al, 2008), and Uygur (Zhang et al, 2006) in China, polymorphism of rs1799983 (G>T) in the eNOS gene was found to be a risk factor of EH, while rs2070744 (T>C) polymorphism lacked an association with EH, in the Chinese Hui ethnic population in this study. Notably, a positive correlation between rs1800780 (A>G) polymorphism and susceptibility to EH was determined here in the Chinese Hui group.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In contrast, the rs2070744 (T>C) variant (T786C mutation) was reported to lack an association with EH in Chinese Kazakh and Japanese groups (Kajiyama et al, 2000;Deng et al, 2007). Consistent with these findings in other ethnic populations, such as Chinese Han (Niu et al, 2011;Chen et al, 2012), Hani (Tang et al, 2008), Yi (Tang et al, 2008), and Uygur (Zhang et al, 2006) in China, polymorphism of rs1799983 (G>T) in the eNOS gene was found to be a risk factor of EH, while rs2070744 (T>C) polymorphism lacked an association with EH, in the Chinese Hui ethnic population in this study. Notably, a positive correlation between rs1800780 (A>G) polymorphism and susceptibility to EH was determined here in the Chinese Hui group.…”
Section: Discussionsupporting
confidence: 53%
“…The EH diagnosis criteria of the World Health Organization (WHO) of 1999 was used to diagnose patients with EH (Chen et al, 2012). The non-EH controls were recruited from the general Hui population and had undergone comprehensive medical screening at the Hospital.…”
Section: Subjectsmentioning
confidence: 99%
“…Если говорить о вошедшем в нашу комбинацию G894T полиморфизме гена eNOS, то, в соответствии с дан-ными современных исследований [43,45], присутствие причинных Т аллелей в генотипе беременных коррели-рует со снижением уровня оксида азота в их крови; при этом минимальные концентрации этого компонента ре-гистрируются у носителей ТТ-генотипа по данному поли-морфизму. Взаимосвязь между данным полиморфизмом и риском развития преэклампсии широко обсуждается в литературе и подтверждена целым рядом исследований [2,8,16,23,37,45].…”
Section: илиunclassified
“…However, results of these investigations are conflicting and controversial. Two meta-analyses [142,143] searched to clarify the associations between these genetic variants and the risk for PE. Chen et al [142] displayed in non-Asian populations (seven studies included) a positive significant association between the intron 4a allele and PE.…”
Section: Genes Involved In Endothelial Dysfunctionmentioning
confidence: 99%
“…Two meta-analyses [142,143] searched to clarify the associations between these genetic variants and the risk for PE. Chen et al [142] displayed in non-Asian populations (seven studies included) a positive significant association between the intron 4a allele and PE. Moreover, homozygosity for the 894T and intron 4a of eNOS were significantly positively associated with PE, especially in non-Asian populations.…”
Section: Genes Involved In Endothelial Dysfunctionmentioning
confidence: 99%